2016
DOI: 10.4025/actasciagron.v38i4.30790
|View full text |Cite
|
Sign up to set email alerts
|

<b>Roots of ‘BRS Princesa’ banana fertigated with humic substances and saponin-based plant extracts

Abstract: ABSTRACT. This study aimed to evaluate the effects of fertigation with humic substances, with and without the addition of plant extracts, on the root system of the 'BRS Princesa' banana cultivar. The banana crop was cultivated at a spacing of 2.0 x 2.5 m and fertigated using a drip system in a dystrocohesive Yellow Latosol. The experimental design was randomized blocks, in a split-split-plot scheme with five replicates, for the following factors: humic substance doses and presence of a plant extract formulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
1
7
0
2
Order By: Relevance
“…The absence of positive effects from the humic substances fertigation on the soil chemical attributes may explain the lack of significant effects on the growth and yield properties of the orchard. This corroborates the findings by Coelho et al (2016), who reported similar results for the agronomic performance of the 'BRS Princesa', during its first production cycle. The average values reported for the biometric variables are presented in Table 6.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The absence of positive effects from the humic substances fertigation on the soil chemical attributes may explain the lack of significant effects on the growth and yield properties of the orchard. This corroborates the findings by Coelho et al (2016), who reported similar results for the agronomic performance of the 'BRS Princesa', during its first production cycle. The average values reported for the biometric variables are presented in Table 6.…”
Section: Resultssupporting
confidence: 92%
“…Coelho et al (2016) studied the drip irrigation of humic substances (doses up to 42.42 L ha -1 cycle -1 ), in a Dystric Densic Xantic Ferralsol cultivated with 'BRS Princesa' banana trees, and found no effects on the plant performance or soil physical-hydraulic attributes, during the first production cycle of the orchard.…”
Section: Palavras-chavementioning
confidence: 99%
“…The absence of effects on banana growth can be related to the response time of the soil to the application of HS, which acted as conditioners of soil chemical and physical quality, improving its capacity of ion exchange, availability of nutrients, and structure (Selim and Mosa, 2012;Coelho et al 2016), but without directly supplying nutrients, such as organic matter in less advanced stages of decomposition, so that their action on plant nutrition and growth is indirect and does not occur immediately. Therefore, their effects may take a longer time in comparison with fertilizers industrially produced for rapid incorporation of nutrients …”
Section: Resultsmentioning
confidence: 99%
“…Besides, the nature of these organic compounds is relatively complex and there is unconsolidated knowledge on the action of the humic fraction on plants due to its composition and chemical structure, which has not been elucidated and is variable (Baldotto and Baldotto, 2014). Another aspect is the doses of HS application, which may not have been sufficient to promote positive responses on banana plants (Hartz and Bottoms, 2010;Lodhi et al, 2013;Coelho et al, 2016;Melo et al, 2016).…”
Section: Ph (Water)mentioning
confidence: 99%
“…Em sinergia, a aplicação dos resíduos vegetais pode ajudar a proteger o solo, atenuar o crescimento de ervas invasoras, conservar água na rizosfera, potencializar a atividade biológica no solo, melhorar a ciclagem de nutrientes, com melhoria da fertilidade do solo no tempo (RESENDE et al, 2005;BORGES et al, 2015;COELHO et al, 2016).…”
Section: Introductionunclassified